Using Short Stories as a Teaching Strategy to Improve Student’s Reading Comprehension - Melati Manurung; Sanggam Siahaan (The Future of Education Journal, 2026)
Reading comprehension is one of the most important skills in English language learning because it enables students to understand, interpret, and analyze information from written texts. However, many students still face difficulties in comprehending English texts due to limited vocabulary, low reading motivation, and ineffective learning strategies. Therefore, teachers need to implement appropriate teaching strategies to improve students’ reading comprehension. This study aims to investigate the use of short stories as a teaching strategy to improve students’ reading comprehension in English language learning. This research employed a library research method by analyzing and synthesizing findings from twenty-five previous studies published between 2021 and 2026. The selected studies were reviewed and categorized into five themes: reading comprehension improvement, reading motivation, vocabulary development, reading strategies, and students’ engagement in reading activities. The findings reveal that short stories significantly contribute to improving students’ reading comprehension by providing meaningful and contextualized language input. In addition, short stories increase students’ motivation to read, enrich vocabulary knowledge, facilitate the use of reading strategies, and encourage active participation during classroom learning activities. The analysis also indicates that students become more interested and engaged in reading lessons when short stories are used as instructional materials. Based on the findings, it can be concluded that short stories are an effective teaching strategy for improving students’ reading comprehension in English language learning. Therefore, English teachers are encouraged to integrate short stories into reading instruction to create more meaningful, enjoyable, and effective learning experiences.